Personal experience of Latin American therapists on their clinical practice during the COVID-19 pandemic (Experiencia personal de terapeutas latinoamericanos sobre su práctica clínica durante la pandemia por COVID-19). Issue 3 (2nd September 2022) - Fernández, Olga; Espinosa, H. Daniel; Krause, Mariane; Altimir, Carolina; Mantilla, Carla; Paz, Clara; Lozano, Arturo G.; Argumedo, Doris; De La Cerda, Cecilia; Juan, Santiago; Fernández, Sofia; Lancho, M. Paz; et al.
ABSTRACT: The health conditions generated by the COVID-19 pandemic severely restricted in-person therapy, and as a result online therapy was put into practice. The objective of this study was to describe and analyse, from the perspective of the therapist, how the pandemic has influenced their experience and clinical practice. Qualitative interviews were conducted with 24 Latin American therapists who had performed online therapy during the pandemic. The information was analysed following the coding procedures of the Grounded Theory. Three core categories were constructed from the analysis: (a) impact on the therapist: spiral of uncertainty, oppression and adaptive astonishment; (b) incorporation of technologies into clinical practice: 'I never thought they could help'; and (c) transformation of the practice of psychotherapy: 'water always finds its way'. The model incorporates and relates therapists' perceptions of their professional work, patients' attitudes towards this new psychotherapy method, perception of the therapeutic relationship and process, and the facilitators and obstacles experienced in online therapy.